(untitled) (Research, Society and Development, 2022)
Objective: To compare the effects of continuous and resistance aerobic training at high intensity and resistance in women with breast cancer during chemotherapry treatment. Design: A randomized clinical trial. Forty patient’s diagnostics with breast cancer and undergoing chemotherapy. Will be recruited and randomized into two groups: (a) Combined training (continuous aerobic + resistance); (b) Combined training (high-intensity interval (IAI) + resistance). They will follow a protocol for inclusion One-Repetition Max Test (1RM), Grocery Shelving Task Test, Shuttle walk test incremental and the questionaries: Quality of life questionarie (EORTC QLQ-C30), Functional Assessment of Cancer Therapy Breast (FACT-B) e Brief Fatigue Inventory (BFI). The training protocol proposed for the study groups should be carried out for 8 weeks, three times a week on alternate days, totaling 24 training sessions. Conclusion: The focus of research in this area has predominantly been over the past two decades, focused on the effectiveness of exercise as an adjuvant strategy after cancer diagnosis. Observational studies indicate that physical exercise is directly linked to a reduction in the risk of cancer recurrence and mortality. We hypothesized that all the training protocols proposed to promote the benefits in health indicators in this study and potential for therapies for patients safely undergoing cancer treatment will present, but which protocol can still pursue the beneficial effect.